ENT endoscopic procedures and aerosolization during COVID-19 pandemic: a review of concepts and guidelines - Patar, Mukul; Borsaikia, Kusum; Islam, Taufeequl (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Otolaryngologists are more prone for exposure to aerosols during routine ENT examination and endoscopic procedures. ENT endoscopy procedures are considered as most aerosol-generating procedures and preferably routine procedures are avoided and deferred, if at all not necessary or urgent at this time of COVID-19 pandemic. The small particle size and extended travel of airborne aerosols mandate the use of specific personal protective equipment (PPE) and barriers by the health care workers to protect against transmission of COVID-19. Studies have recommended ENT endoscopy in awake patients with adequate topical preparation for local anaesthesia. Use of sprays should be avoided, instead, carefully placed pledgets should be used to provide adequate decongestion and anesthesia. Well ventilated endoscopy room with negative pressure (preferably), wearing a N95 mask with face shield or full PPE, thorough cleaning of entire endoscope after removal by standard disinfectants, decontamination of endoscopy room after each procedure and proper disposal of contaminated waste products are some common guidelines advised by health authorities globally till date.